2013
DOI: 10.1177/1757975913501209
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of perceptions on tobacco in vulnerable populations between India and France

Abstract: Abstract:Perceptions of tobacco are a relatively unexplored issue in disadvantaged populations in India and France. The objectives of this study included the following: obtain qualitative information on representations of tobacco use and cessation within two vulnerable populations; identify cultural factors that influence tobacco use and cessation; and acquire information for the development of effective tobacco cessation strategies. A total of 21 focus groups were conducted in India and France. All study part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This is in contrast to another study conducted in France and India, wherein most participants felt quitting tobacco was a challenge. [22] Thus, the present study among urban low socioeconomic women in Mumbai, India shows high prevalence of smokeless tobacco. The use of masheri is especially popular among these women.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This is in contrast to another study conducted in France and India, wherein most participants felt quitting tobacco was a challenge. [22] Thus, the present study among urban low socioeconomic women in Mumbai, India shows high prevalence of smokeless tobacco. The use of masheri is especially popular among these women.…”
Section: Discussionmentioning
confidence: 58%
“…This is in contrast to another study conducted in France and India, wherein most participants felt quitting tobacco was a challenge. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…The use of a composite dependent-variable index of addictive behaviors also provided a more comprehensive approach than one which examined each addictive activity separately (although these data have been provided as supplementary information). This strategy is particularly relevant since preferences for specific addictive activities are known to vary across sociocultural groups ( 59 61 ). In addition, while other studies have examined personality correlates of ADHD – in particular, those also associated with risk for addiction – as reviewed in the Section “ Introduction ,” this body of work has largely investigated constructs related to impulsive responding.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study among 60 disadvantaged women smokeless tobacco users in Delhi, participants expressed that seeing others around them chewing tobacco would pose a challenge to quitting. 25 On the other hand, the ITC Four Country Survey found that smokers who lost touch with smoking friends between two waves of the survey were significantly more likely to have attempted to quit (OR= 1.5; p< 0.0001) and to have quit successfully (OR= 1.6; p< 0.01) than those who did not lose any smoking friends during the period. 26 …”
Section: Discussionmentioning
confidence: 97%